(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
Golestan Region has a big potential for ecotourism development. Nowadays the usage of this potential is not on a sufficient level. For solving this problem there must be a strategy. The results of their research can serve as a framework for creating a strategy of ecotourism development. This strategy will be based on the usage of natural potential of the territory. At the same time, the strategy will include the complex usage of society capacity based on present and future interests.